Phonological awareness in two groups at first elementary grade students of public and subventioned schools - Aravena T., Jeniffer (Revista Chilena de Fonoaudiología, 2014)
The aim of this study was to describe the phonological awareness performance in students starting first grade in elementary school, considering the type educational institution they attend. The study group consisted of 100 Chilean children, low socioeconomic status, enrolled in public schools and state-funded private schools in the Metropolitan Region. The development of phonological awareness was assessed using a test for phonological awareness. The results show that, at the beginning of first grade, 56% of students show a low development of phonological awareness. In addition, the analysis of the level of performance on each sub-test shows significant differences linked to the complexity of the tasks. Furthermore, it was found that students attending state-funded private schools performed better in phonological awareness than students in public schools.